"Development of Technology and Science as a Need for the Future of Education: Philosophy of Science" - Afasli, Bunga; Solfema, Solfema; Karneli, Yeni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Technological advances have had a significant impact on the world of education, especially in the learning process. Information and Communication Technology (ICT), as part of science and technology (IPTEK), includes all technologies related to the retrieval, collection (acquisition), processing, storage, dissemination, and presentation of information. Even until the beginning of the 21st century, it is believed that the ICT field will continue to grow rapidly and has not shown signs of saturation for the next few decades. At the global level, the development of ICT has affected every aspect of human life. The integration of ICT into various fields of technology has reached such a level that there is not a single piece of equipment resulting from technological innovation that does not utilize ICT devices.